The first ITS2 sequence data set of eDNA from honey of Malaysian giant honeybees (Apis dorsata) and stingless bees (Heterotrigona itama) reveals plant species diversity - Huda, Nurul; Ullah, Saeed; Abdul Wahab, Roswanira; Lani, Mohd Nizam; Abu Daud, Nur Hardy; Mohd Shariff, Amir Husni; Ismail, Norjihada Izzah; Abdul Hamid, Azzmer Azzar; Mohamad, Mohd Azrul Naim; Huyop, Fahrul Zaman (Springer Nature, 2023)
Objectives Pollen is a useful tool for identifying the provenance and complex ecosystems surrounding honey production in Malaysian forests. As native key pollinators in Malaysia, Apis dorsata and Heterotrigona itama forage on various plant/pollen species to collect honey. This study aims to generate a dataset that uncovers the presence of these plant/pollen species and their relative abundance in the honey of A. dorsata and H. itama. The information gathered from this study can be used to determine the geographical and botanical origin and authenticity of the honey produced by these two species. Results Sequence data were obtained for both A. dorsata and H. itama. The raw sequence data for A. dorsata was 5 Mb, which was assembled into 5 contigs with a size of 6,098,728 bp, an N50 of 15,534, and a GC average of 57.42. Similarly, the raw sequence data for H. itama was 6.3 Mb, which was assembled into 11 contigs with a size of 7,642,048 bp, an N50 of 17,180, and a GC average of 55.38. In the honey sample of A. dorsata, we identified five different plant/pollen species, with only one of the five species exhibiting a relative abundance of less than 1%. For H. itama, we identified seven different plant/pollen species, with only three of the species exhibiting a relative abundance of less than 1%. All of the identified plant species were native to Peninsular Malaysia, especially the East Coast area of Terengganu. Data description Our data offers valuable insights into honey’s geographical and botanical origin and authenticity. Metagenomic studies could help identify the plant species that honeybees forage and provide preliminary data for researchers studying the biological development of A. dorsata and H. itama. The identification of various flowers from the eDNA of honey that are known for their medicinal properties could aid in regional honey with accurate product origin labeling, which is crucial for guaranteeing product authenticity to consumers.